La implementación del principio de ciudadanía universal en la constitución de Ecuador de 2008 (2013)
This paper presents a reflection around the theoretical and political process of the institutionalization of the principle of Universal Citizenship in the Constitution of Ecuador of 2008. To achieve this goal, the work addresses four points. The first one consists of a theoretical approach to the issue of citizenship, the second one explores the new Latin American constitutionalism as a possible framework for understanding this institution and the regional circumstances surrounding the 2008 constitution; the third section describes the internal circumstances of Ecuador that led to the adoption of this principle; and finally, it recapitulates the Ecuadorian experience and constitutional provisions that formalized its inclusion.